The universe of group representation in Germany: Analysing formal and informal party rules and quotas in the process of candidate selection. Issue 1 (January 2014) - Reiser, Marion
The main aim of this article is to develop a perspective on the universe of measures for group representation that goes beyond a narrow focus on gender and ethnicity. The article employs an inductive approach by analysing and comparing the formal and informal party quotas and rules applied by political parties in candidate selection processes for the German federal elections using a mixed-method design of qualitative interviews, content analysis and participant observation. The analysis reveals that parties in Germany adopt a broad range of party rules to guarantee group representation, which differ systematically by party type and ideology. Overall, there is a predominance of informal, yet highly institutionalised, quotas and rules. Also, there are clear conflicts as to the relative ranking of specific quotas and rules, leading to interaction effects between them. Based on this neo-institutionalist perspective, the article then attempts to develop a typology of quotas.